Anka and Milan – Letters of Dr Milan Dimitrijević in the Archives of the Serbian Academy of Sciences and Arts - Spasović, Ivana (Napredak, 2023)
The paper presents the letters of Dr Milan Dimitrijević and his family, kept in the Archives of the Serbian Academy of Sciences and Arts, in the legacy of Patriarch German Anđelić (1822-1888). Milan Dimitrijević (1844-1901) was a teacher in the Grammar School in Sremski Karlovci and a reliable associate of Patriarch German. This correspondence reveals the biographies of Dimitrijević and his wife, and also offers a new insight into the political scene in Hungary of the 1880s and 1890s.